2023
DOI: 10.1021/acs.chemmater.3c00634
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Spinels with Superior Mg Conductivity

Abstract: Mg batteries with oxide cathodes have the potential to significantly surpass existing Li-ion technologies in terms of sustainability, abundance, and energy density. However, Mg intercalation at the cathode is often severely hampered by the sluggish kinetics of Mg2+ migration within oxides. Here we report a combined theoretical and experimental study addressing routes to identify cathode materials with an improved Mg-ion mobility. Using periodic density functional theory calculations, Mg2+ migration in oxide sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
(104 reference statements)
1
5
0
Order By: Relevance
“…The spinel structure possesses a desirable combination of capacity and voltage. [87] Recent studies [101,102] have reported experimental migration barriers of approximately 600 meV for Mg 2+ in Cr-and Mn-spinel oxides, aligning with DFT calculations. It has been observed that structural disorder within the spinel lattice affects the migration of Mg ions, and this disorder can be regulated during synthesis.…”
Section: Spinelssupporting
confidence: 57%
See 3 more Smart Citations
“…The spinel structure possesses a desirable combination of capacity and voltage. [87] Recent studies [101,102] have reported experimental migration barriers of approximately 600 meV for Mg 2+ in Cr-and Mn-spinel oxides, aligning with DFT calculations. It has been observed that structural disorder within the spinel lattice affects the migration of Mg ions, and this disorder can be regulated during synthesis.…”
Section: Spinelssupporting
confidence: 57%
“…The discovery of these scaling relations has significant implications as it shows the potential to accelerate the process of finding materials with desired ion mobility properties such as oxide spinels. [87] By utilizing this approach, researchers can more efficiently explore and identify materials that exhibit enhanced ion mobility, thus contributing to the development of improved electrochemical devices, including batteries and solid electrolytes.…”
Section: Descriptors and Design Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the facts that Prussian Blue is a double perovskite type material and that octahedral tilting in Perovskites has been extensively studied, it is known that a phase of this symmetry has to be formed by a cooperative out-of-phase rotation of the FeC 6 and FeN 6 octahedra in all three directions of space (a À a À a À rotation after Glazer). [26][27][28][29][30][31] Such a rotation often causes the trigonal distortion, [32,33] which further splits the d-orbitals by forming one a 1g and two e' g states out of the already favourable t 2g -states. The a 1g state is further lowered in energy in comparison to both the barycenter and the t 2g -states.…”
Section: Basic Electronic Configurationmentioning
confidence: 99%